Heat wave event facilitates defensive responses in invasive C3 plant Ambrosia artemisiifolia L. under elevated CO2 concentration to the detriment of Ophraella communa - Tian, Zhenya; Ma, Chao; Zhao, Chenchen; Zhang, Yan; Gao, Xuyuan; Tian, Zhenqi; Chen, Hongsong; Guo, Jianying; Zhou, Zhongshi (Frontiers in Plant Science, 2022)
To predict and mitigate the effects of climate change on communities and ecosystems, the joint effects of extreme climatic events on species interactions need to be understood. Using the common ragweed (Ambrosia artemisiifolia L.)—leaf beetle (Ophraella communa) system, we investigated the effects of heat wave and elevated CO2 on common ragweed growth, secondary metabolism, and the consequent impacts on the beetle. The results showed that elevated CO2 and heat wave facilitated A. artemisiifolia growth; further, A. artemisiifolia accumulated large amounts of defensive secondary metabolites. Being fed on A. artemisiifolia grown under elevated CO2 and heat wave conditions resulted in the poor performance of O. communa (high mortality, long development period, and low reproduction). Overall, under elevated CO2, heat wave improved the defensive ability of A. artemisiifolia against herbivores. On the other hand, enhanced adaptability to climatic changes may aggravate invasive plant distribution, posing a challenge to the control of invasive plants in the future.